Al-Ijtihād al-Intiqā'ī and the Resolution of Issues in the Schools of Islamic Jurisprudence: A Study on the Implementation of the Concept of Al-Ijtihād al-Intiqā'ī in the Indonesian Religious Courts. - Farhan Istiqlal, Ibnu; Fadlilah, Meriza Isna; Akhdza. E, M. Ikhsanul (Rayah Al-Islam, 2025)
The dynamic development of the times has given rise to various new legal issues, including in the realm of Islamic family law. In this context, ijtihad becomes an important instrument to find legal solutions relevant to contemporary conditions. This study specifically examines the application of ijtihad intiqa'i in the settlement of cases in Religious Courts in Indonesia, where there are differences of opinion among the schools of Islamic law. This study uses a qualitative approach with a case study method. Primary data was obtained through a study of documents of the Religious Court's decisions and Islamic jurisprudence books as material for analysis. Data analysis was conducted using the theoretical framework of ijtihad intiqa'i. The results of the study show that ijtihad intiqa'i has been applied by judges in settling cases, especially in cases involving differences of opinion among the schools of thought, such as the provision of iddah allowance for women who have been divorced ba'in. Judges tend to choose the opinion that is most appropriate to social, cultural, and justice conditions. However, in practice, there are still some obstacles in the application of ijtihad intiqa'i, such as a lack of in-depth understanding of the theory of ijtihad, limited resources, and social pressure. This study concludes that ijtihad intiqa'i has a very important role in the dynamics of Islamic law in Indonesia. However, more systematic efforts are needed to improve the capacity of judges in carrying out ijtihad, as well as the provision of clearer regulations regarding the application of ijtihad in religious courts.